Characterization of Seed Oils of Pterodon emarginatus Vogel (Sucupira) Obtained by Different Extraction Methods - Costa-Singh, Tainara [UNESP]; Jorge, Neuza [UNESP] (Inst Tecnologia Parana, 2019)
The present study aims to evaluate the influence of extraction methods on the quality of bioactive compounds and antioxidant capacity in Pterodon emarginatusVogel (sucupira) oils. The oils were extracted from the sucupira seeds by Soxhlet and by the extraction system of Bligh & Dyer. The oils were analyzed as to fatty acid profile, tocopherols, phytosterols, carotenoids, total phenolics, and total antioxidant capacity. The extraction by Soxhlet showed better yield of total lipids and was more efficient to extract tocopherols, phytosterols, and carotenoids, besides presenting better antioxidant activity by DPPH center dot. However, this method showed insufficient capacity to extract the polar lipid components of the sample, as evidenced by the low results of total phenolic compounds. On the other hand, the Bligh & Dyer method preserved the fatty acid profile and was also effective to extract higher phenolic compounds content and presented superior antioxidant activity when assessed by FRAP, ABTS(center dot+), and oxidative stability index.
Keywords: Antioxidants; Bioactives; Extraction; Oxidative stability; Chromatography